Static Scaling in the CePd3Bx Kondo system - Kappler, J. P.; Nieva, G.; Sereni, J.G.; Souletie, J.; Sereni, Julián; Nieva, Gladys (EDP Sciences, 1988)
Fil: Nieva, G. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina